A conceptual framework for improving effectiveness of risk management in supply networks - Chaudhuri, Atanu; Ghadge, Abhijeet; Gaudenzi, Barbara; Dani, Samir (Emerald, 2020)
Purpose The purpose of the paper is to develop a conceptual framework for improving the effectiveness of risk management in supply networks following a critical literature review. Design/methodology/approach A critical review of 91 scholarly journal articles published between 2000 and 2018 supports the development of an integrated conceptual framework.
Keywords: Conceptual framework; Supply network characteristics; Supply chain integration; Supply chain risk management